(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Every journey starts from a desire that is at the same time the drive towards appropriation and the awareness of an impossible fulfillment. Through the image of the baby pointing the finger on the map designating an unknown place – the blank space – that he will want to reach when he will grow up, Joseph Conrad defines a paradigm that will be later recovered and remodeled by other authors. This essay follows the steps of Marlow in Heart of Darkness, in order to rediscover his tracks in actors such as Iain Sinclair and Will Self, in the attempt to build a relationship of contiguous desires to which literature has, over time, given body and substance, a fragile and impermanent substance that is, in a Shakespearian way, the matter which dreams are made by.